Lack of early improvement with antipsychotics is a marker for subsequent non-response in behavioral and psychological symptoms of dementia: Analysis of CATIE-AD data - Yoshida, Kazunari (Am J Geriatr Psychiatry, 2017)
OBJECTIVE: Prediction of response/non-response to antipsychotics is especially important in patients with behavioral and psychological symptoms of dementia (BPSD) in whom antipsychotic exposure increases risks of death. We aimed to examine whether presence/absence of early improvement of BPSD with antipsychotics is associated with subsequent response/non-response. DESIGN: Post-hoc analysis of the Clinical Antipsychotic Trials in Intervention Effectiveness with Alzheimer’s Disease (CATIE-AD) study (2001–2004) (trial registration: NCT00015548). SETTING: 45 sites in the United States. PARTICIPANTS: 245 subjects (olanzapine, n=90; quetiapine, n=81; risperidone, n=74) with a DSM-IV diagnosis of dementia of the Alzheimer’s type who presented with a score of 1 or more in the Brief Psychiatric Rating Scale (BPRS) at baseline (Phase 1 of CATIE-AD). INTERVENTION: Subjects were randomly assigned to treatment with olanzapine, quetiapine, risperidone, or placebo in a double-blind manner. MEASUREMENTS: We examined associations between response at week 8, and demographic and clinical characteristics, including BPRS total score reduction at week 2, using logistic regression analyses. Prediction performance of binary classification (presence/absence) of improvement/no improvement at week 2 for response at week 8 was examined. RESULTS: BPRS total score reduction at week 2 (mean percentage score reduction, 12.6%) was significantly associated with response at week 8 (odds ratio, 1.18; 95% CI, 1.11–1.26). The 5% score reduction cut-off at week 2 showed the highest accuracy (0.71) with sensitivity, specificity, PPV, and NPV of 0.76, 0.65, 0.69, and 0.72, respectively. CONCLUSION: Lack of even a very small early improvement with antipsychotic treatment may be a marker of subsequent non-response in BPSD.